K.H. AHMAD DAHLAN AND CREATIVE PRODUCTIVE INSTRUCTIONAL METHOD - Setyarini, Tri; Jamuin, Ma?arif; Ali, Mohamad (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2018)
This present study investigates a model of Muhammadiyah education developed by K.H. Ahmad Dahlan. In the midst of a creativity and productivity crisis in Indonesia, it is challenging to divulge the concept of creative-productive learning model since it is a potential basis to build creative and productive characters. As one of prominent Islamic scholars, K.H. Ahmad Dahlan is outstanding for his progressive view, including in the fields of education and instructional. He has shifted the former Sorogan system into the classical system and implemented it in his educational activities, as well as introduced creative-productive learning model. The concept of K.H. Ahmad Dahlan?s creative-productive learning and its relevance with the 2013 Curriculum will be discussed in this study.